2010 International WaterSide Security Conference 2010
DOI: 10.1109/wssc.2010.5730228
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Capability Requirements as derived from the Long Term Requirements Study

Abstract: Of the 38 Long Term Capability Requirements indentified by NATO in the 2009 Long Term Requirements Study, at least four can be directly applied to waterside security research and technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study aimed to develop a sequence prediction model that performs the best result. There are five steps to establish a simple RNN model (Figure 4) and LSTM model (Figure 5), as follows [24]:…”
Section: Development Of Recurrent Neural Network (Rnns) Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to develop a sequence prediction model that performs the best result. There are five steps to establish a simple RNN model (Figure 4) and LSTM model (Figure 5), as follows [24]:…”
Section: Development Of Recurrent Neural Network (Rnns) Modelsmentioning
confidence: 99%
“…The result showed that both LSTM and RNN models fit the sequence data because training loss decreased over time, achieving low error values. A good fit is determined by a training and validation loss that decreases to the point of constancy with a minimal gap between the two ending loss values[24]. Moreover, the loss of the model should be lower on the training set than on the test set.…”
mentioning
confidence: 99%
“…Another issue addressed during the preparation was how to deal with the time series data and prepare it correctly for the algorithm. In the case of applications such as neural networks, we have tools for time series, or a suitable type, called long-short term memory (LSTM) networks (Brownlee, 2017). In conventional machine learning methods, especially supervised learning, we will certainly want to see what the importance of each observation term for forecasting is, etc.…”
Section: Creating Shifted Valuesmentioning
confidence: 99%